The Power To Heal : Ancient Arts & Modern Medicine - Smolan, Rick (et al.) (New York Prentice Hall Press, 1990)
This exploration of healing moves from ancient techniques and primitive treatments to the frontiers of medical technology, including miracle pharmaceuticals, unique health regimes, incredible recoveries, unusual birthing practices and the secrets of remarkable centenarians. Combining essays from some of America's foremost writers this book looks at some of the most important topics in the world of medicine.
Include Color Illustrations
Keywords: Medicine